Distributed Economic Model Predictive Control-Based Self-Powered Active Vibration Control of Flexible Structures With PMSM Electromagnetic Damper - Kaixin Cheng; Yuanbo Guo; Ze Li; Qigang Liang; Luyu Li; Xiaohua Zhang (IEEE Open Journal of the Industrial Electronics Society, 2025)
In this article, a new type of self-powered active mass damper (SPAMD) based on permanent magnet synchronous motor is designed for large-scale flexible structure vibration reduction systems. SPAMD can fully utilize the characteristics of four-quadrant operation of the motor, enabling active suppression of structural vibration while recovering energy. To achieve active vibration reduction control, a distributed control strategy of multiple energy-interconnected self-powered active mass dampers is proposed. Therein, a multilevel substructure method is employed to allocate actuators across different levels of the substructure systems. In addition, a distributed economic model predictive control (DEMPC) strategy is presented to optimize control inputs, which can ensure that the flexible structural system achieves optimal energy recovery power while satisfying certain state constraints. Consequently, the coordinated control of system performance and energy recovery is achieved under self-powered conditions. Extensive experiments on the dSPACE DS1006 platform are carried out to verify the feasibility of the proposed DEMPC method.